The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.omto.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs and circular RNAs in tumor angiogenesis: From mechanisms to clinical significance

Abstract: Long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) execute a wide array of functions in physiological and pathological processes, including tumor progression. Angiogenesis, an elaborate multistep process driving new blood vessel formation, accelerates cancer progression by supplying nutrients and energy. Dysregulated lncRNAs and circRNAs can reportedly impact cancer progression by influencing angiogenesis. However, the expanding landscape of lncRNAs and circRNAs in tumor progression-dependent angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 179 publications
(211 reference statements)
2
23
0
Order By: Relevance
“…Furthermore, certain inhibitors (such as bevacizumab) can markedly decrease the expression of angiogenic factors (VEGF), thereby inhibiting angiogenesis 65 . Therefore, advancing our current understanding of the cellular and molecular mechanisms associated with tumor angiogenesis will enable the development of novel anti-angiogenic therapies 66 .…”
Section: Functions Of Exosomal Circrnas In the Tmementioning
confidence: 99%
“…Furthermore, certain inhibitors (such as bevacizumab) can markedly decrease the expression of angiogenic factors (VEGF), thereby inhibiting angiogenesis 65 . Therefore, advancing our current understanding of the cellular and molecular mechanisms associated with tumor angiogenesis will enable the development of novel anti-angiogenic therapies 66 .…”
Section: Functions Of Exosomal Circrnas In the Tmementioning
confidence: 99%
“…Angiogenesis is a key factor in tumor growth, invasion and metastasis. It is partly mediated by the transcription factor NF-κB and pro-angiogenic factors (including VEGF, IL-8, COX-2 and MMP-9) (Ferrara and Kerbel, 2005;Liu et al, 2021). Dihydroartemisinin showed anti-angiogenic effect in both in vitro angiogenesis models and in vivo pancreatic cancer-derived tumor models (Wang et al, 2011).…”
Section: Inhibition Of Angiogenesismentioning
confidence: 99%
“…Animal xenograft models showed that the combination of artemisinins with onconase (Shen et al, 2016), gemcitabine (Yang et al, 2019a), carboplatin (Chen T. et al, 2009), cisplatin (Zhang YJ. et al, 2013;Li W. et al, 2021), doxorubicin (Tai et al, 2016), Apo2L/TRAIL (Kong et al, 2012), allicin (Jiang et al, 2013), cytarabine (Drenberg et al, 2016), sorafenib (Jeong et al, 2015;Jing et al, 2019), triptolide [17], and temozolomide (Berte et al, 2016) can exert a synergistic effect on leukemia (Drenberg et al, 2016), renal cell carcinoma (Jeong et al, 2015), glioblastoma (Berte et al, 2016), lung (Zhang YJ. et al, 2013;Shen et al, 2016;Li W. et al, 2021), ovarian (Chen T. et al, 2009;Yang et al, 2019a), cervical (Tai et al, 2016), pancreatic (Kong et al, 2012;Liu and Cui, 2013), and liver (Jing et al, 2019) cancer.…”
Section: Combination Therapymentioning
confidence: 99%
See 2 more Smart Citations